Systematic literature review on the application of additive manufacturing in repair and restoration - Maidin, Shajahan; Rajendran, Thavinnesh Kumar; Ismail, Shafinaz; Mohd Ali, Latifah (Universiti Teknologi Malaysia, 2023)
The process of repair and restoration is crucial to environmental sustainability as it allows parts or products to be reinstated like a new condition before moving on to the next stage of their life cycles. Presently, skilled workers manually do these tasks. With the introduction of additive manufacturing (AM), people are exploring its possibilities for automated repair and restoration, making it a more efficient technique for remanufacturing. This systematic review aims to identify the application of AM specifically in repair and restoration. The search was carried out using all accessible electronic databases. 75 articles were found that fulfilled the search criteria. The gap in each article was discovered, to provide comprehensive coverage of repairing techniques of parts made of the same or different materials. The findings show that AM technology heralds a new era of repairability. Using AM for repair and restoration shows promising results, motivating more research. In addition, AM shows transformational potential for creating, making, distributing, and repairing goods. Printing replacement components is an example of a step toward this transition. AM provides a rapid and effective repair solution when product malfunctions and specific replacement components are unavailable or limited